Assembly of two novel coordination polymers by selecting ditopic or chelating auxiliary ligands with naphthalene‐2, 6‐dicarboxylic acid: synthesis, structure and luminescence sensing. Issue 12 (24th November 2020) - Zuo, Yuxiang; Yang, Jie; Chen, Cheng; Xue, Yun-Shan; Zhang, Jun
Abstract : To develop more crystalline chemical sensors for the selective detection of Fe 3+, two novel two‐dimensional (2D) coordination polymers of naphthalene‐2, 6‐dicarboxylic acid have been prepared using solvothermal methods, one of which exhibits highly selective sensing for the Fe 3+ ion. Abstract : The Fe III ion as a ubiquitous metal plays a key role in biochemical processes. Iron deficiency or excess in the human body can induce various diseases. Thus, effective detection of the Fe III ion has been deemed an issue of focus. To develop more crystalline chemical sensors for the selective detection of Fe 3+, two novel two‐dimensional (2D) coordination polymers, namely, poly[[[μ‐bis(pyridin‐4‐yl)amine‐κ 2 N : N ′](μ‐naphthalene‐2, 6‐dicarboxylato‐κ 2 O 2 : O 6 )zinc(II)] 0.5‐hydrate], [Zn(C12 H6 O4 )(C10 H9 N3 )]·0.5H2 O n, 1, and poly[(4, 4′‐dimethyl‐2, 2′‐bipyridine‐κ 2 N, N ′)(μ‐naphthalene‐2, 6‐dicarboxylato‐κ 2 O 2 : O 6 )hemi(μ‐naphthalene‐2, 6‐dicarboxylic acid‐κ 2 O 2 : O 6 )copper(II)] [Cu(C12 H6 O4 )(C12 H12 N2 )(C12 H8 O4 )0.5 ] n, 2, have been prepared using solvothermal methods. Single‐crystal X‐ray diffraction analysis shows that compound 1 is an undulating twofold interpenetrated 2D (4, 4)‐sql network and compound 2 is a twofold interpenetrated 2D honeycomb‐type network with a (6, 3)‐hcb topology. In addition, 1 exhibits highly selective sensing for the Fe 3+ ion.